Effectiveness of Learning at MTsN 3 Jombang: Online Learning During The Covid-19 Pandemic - M Wafiyul Ahdi; M Ichya Ulumuddin (SCHOOLAR: Social and Literature Study in Education, 2021)
The impact of the spread of Covid-19 has led to the implementation of online or online learning. Online learning is learning that is carried out using electronic technology, including Islamic Religious Education which must also conduct online learning. So far, Islamic education has often used face-to-face methods and few have used technology. The objectives of this research are: 1) To analyze the impact of Covid-19 on the effectiveness of Islamic religious education 2) to find out the effectiveness of online learning in the midst of a social distancing situation. The research method used is a qualitative method in the form of contextual library exploration, namely linking literature with actual phenomena, especially Covid-19. The collection of this research is to collect relevant books, journals. Data collection techniques were carried out by interviewing religious teachers at MTsN 3 Jombang. Whether or not an online learning is effective depends on the technology, the character of the teacher, and the characteristics of the students. Online learning in the midst of a social distancing situation, there are obstacles to the lack of a spiritual approach from teachers to students, even though the facilities and infrastructure provided by Madrasah Tsanawiyah Negeri 3 Jombang are adequate, and training for teachers who are not proficient in using technology and social media is provided. Keywords: Islamic Education, Online Learning, Covid Pandemic,